Within Judaism?: Interpretive trajectories in Judaism, Christianity, and Islam from the first to the twenty-first century - Zetterholm, Karin; Runesson, Anders (Lexington Books/Fortress Academic, 2024)
"The volume charts the shifting boundaries of Judaism from antiquity to the modern period to bring clarity to what scholars mean when they claim that ancient texts or groups are "within Judaism" as well as exploring how rabbinic Jews, Christians, and Muslims have constructed Judaism to form their own identities"--